(untitled) (INDIAN JOURNAL OF VOCATIONAL EDUCATION, 2022)
The purpose of this paper is to investigate the TVET culture, Qualification Framework, TVET institutes, formal-informal structures, SDG successes, policies/programs, and future initiatives in the Australian Context. The article then delves into the financing, difficulties, reforms, and best practices that have an impact on the development and the future of TVET. The information was gathered from secondary sources such as UNESCO and other publications, books, journals, newspapers, existing literature, and data from numerous platforms. The research is primarily qualitative. It is an attempt to assess the current state of VETS in the country.